SYSTEMATIC LITERATURE REVIEW: ANALISIS IMPLEMENTASI KURIKULUM BERBASIS OUTCOME-BASED EDUCATION (OBE) DI PERGURUAN TINGGI - Muhamad Suhardi (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACK The increasing demand for higher education graduates who are capable of adapting to the evolving workforce has encouraged universities to strengthen competency-oriented curricula. In this context, Outcome-Based Education (OBE) has emerged as an educational approach that positions learning outcomes as the foundation for curriculum planning, instructional delivery, and learning assessment. This study synthesizes evidence on the implementation of OBE-based curricula in higher education using a Systematic Literature Review (SLR) approach. The literature search followed the PRISMA 2020 guidelines through the stages of identification, screening, eligibility, and inclusion, drawing data from Google Scholar, Scopus, and ScienceDirect. From approximately 1,100 initially identified articles, 32 met the eligibility criteria, and 25 were selected as the final data sources. The synthesis indicates that the implementation of OBE contributes to improving educational quality through the alignment of learning outcomes, teaching strategies, and assessment practices that support the development of graduate competencies. Nevertheless, its effectiveness remains influenced by lecturers’ readiness, competency-based assessment practices, and institutional support. The findings suggest that the successful implementation of Outcome-Based Education depends not only on curriculum development but also on the integration of academic components that collectively establish a learning outcomes-oriented educational ecosystem. ABSTRAK Tuntutan terhadap lulusan perguruan tinggi yang mampu beradaptasi dengan perubahan dunia kerja mendorong penguatan kurikulum yang berorientasi pada pencapaian kompetensi. Dalam konteks tersebut, Outcome-Based Education (OBE) berkembang sebagai pendekatan yang menempatkan learning outcomes sebagai landasan utama perencanaan, pelaksanaan, dan evaluasi pembelajaran. Kajian ini menyusun sintesis mengenai implementasi kurikulum berbasis OBE di perguruan tinggi melalui pendekatan Systematic Literature Review (SLR). Proses penelusuran literatur mengikuti pedoman PRISMA 2020 dengan tahapan identification, screening, eligibility, dan inclusion menggunakan basis data Google Scholar, Scopus, dan ScienceDirect. Dari sekitar 1.100 artikel yang teridentifikasi, proses seleksi menghasilkan 32 artikel yang memenuhi tahap kelayakan, kemudian ditetapkan 25 artikel sebagai sumber data akhir. Sintesis menunjukkan bahwa implementasi OBE memberikan kontribusi terhadap peningkatan kualitas pembelajaran melalui keterpaduan capaian pembelajaran, strategi pembelajaran, dan asesmen yang mendukung pengembangan kompetensi lulusan. Di sisi lain, efektivitas implementasinya masih dipengaruhi oleh kesiapan dosen, pengembangan asesmen berbasis kompetensi, serta dukungan kelembagaan. Kajian ini menegaskan bahwa keberhasilan Outcome-Based Education tidak hanya ditentukan oleh pengembangan kurikulum, tetapi juga oleh integrasi berbagai komponen akademik yang membentuk ekosistem pembelajaran berbasis learning outcomes.